Anglerfish (Lophius spp.) increasing discards in Spanish OTB fleet (VI-VII ICES). Juveniles availability or sampling artefact? - Santos-Blanco, Juan; Salinas-Aguilera, Miren Itxaso; Araujo-Fernández, María Hortensia; Pérez-Contreras, María Nélida (2011)
An update of the yearly estimates of angler sh (black angler (Lophius budegassa) and white angler(Lophius piscatorius) discarded by the Spanish bottom trawl operating in the Northeast Atlantic ocean are presented. Black angler discards increased sharply in the last three year, while UShape with a maximum in 2010 is found for white angler. A 2003 - 2010 sampling methodology review has beeen carried out without detecting any shift in the protocol which could produce overestimation for recent years discards. Fishing covariates related to black angler discard data also indicates that shing practices remain stable along the series. We detect a steady increase in the species rst length of retention L50 from 21; 5cm in 2003 to a range 23cm - 25cm between 2004 - 2008 and 28cm since 2009. We conclude that interaction between the industry adoption of a Minimum Weigth Landing (500g) and the strength of recruitment indices explain the increase in amounts of angler discards.